The challenges of platform capitalism: Understanding the logic of a new business model. Issue 4 (March 2017) - Srnicek, Nick
Abstract : The platform business model is predicated upon a voracious appetite for data that can only be sated by disregard for privacy (and often workers' rights), and constant outward expansion. As they become ever more central to the global economy, Nick Srnicek argues that it's incumbent on us to understand how they function.